Mangrove Community Structure On The Coast Of Tanjung Kelapa, Tombariri Districts, Bunaken National Park - daud, fitran; Kusen, Janny D.; Kumampung, Deislie Roxmerie H.; Djamaaludin, Rignolda; Darwasito, Suria; Ompi, Medy (Sam Ratulangi University, 2023)
Mangrove ecosystems are wetland resources in coastal areas, life support systems and natural wealth of very high value. The lack of information about the status of mangrove species at the study site as well as the alleged presence of various types of mangrove loss in each region have been identified as important mangrove knowledge information gaps. This can improve various conservation and management strategies, especially in maintaining the sustainability of mangrove ecosystems. This activity lasted 6 (six) months including data collection using the line transect method, the results showed that there were 5 types of mangroves at three stations including Soneratia alba, Rhizophora apiculata, Rhizophora stylosa, Avicennia marina and ceriops tagal. High diversity (H') is found at Station 2 and Station 3 with a Dominance value (D) categorized as moderate at Station 1 while Stations 2 and 3 are categorized as medium, Uniformity (e) at all stations is high, absolute density is highest at station 1 and station 2, and at station 3 the absolute density is lowest, the similarity of community (IS) mangrove types in all three locations is the same because it still includes the same location in the intertaidal area. Keywords: Community structure, Mangrove, Tanjung Kelapa Abstrak Ekosistem mangrove merupakan sumber daya lahan basah pada wilayah pesisir, sistem penyangga kehidupan dan kekayaan alam yang nilainya sangat tinggi.. Kurangnya informasi tentang status spesies mangrove di lokasi penelitian serta dugaan adanya berbagai jenis kehilangan mangrove di setiap wilayah telah diidentifikasi sebagai kesenjangan informasi pengetahuan tentang mangrove yang penting. Hal ini dapat meningkatkan berbagai strategi konservasi dan pengelolaan, terutama dalam menjaga keberlangsungan ekosistem mangrove. Kegiatan ini berlangsung 6 (enam) bulan termasuk dengan pengambilan data mengunakan metode transek garis, Hasil penelitian menunjukan Terdapat 5 jenis mangrove pada ketiga stasiun diantaranya Soneratia alba, Rhizophora apiculata, Rhizophora stylosa, Avicennia marina dan ceriops tagal. Keanekaragaman tinggi (H’) terdapat pada Stasiun 2 dan Stasiun 3 dengan nilai Dominansi (D) dikategorikan sedang pada Stasiun 1 sedangkan Stasiun 2 dan 3 dikategorikan sedang, Keseragaman (e) pada semua stasiun tinggi, kepadatan mutlak tertinggi pada stasiun 1 dan stasiun 2, dan pada stasiun 3 kepadatan mutlak terendah, kesamaan komunitas (IS) jenis mangrove pada ketiga lokasi sama karena masih mencakup satu lokasi yang sama didaerah intertaidal. Kata kunci: Struktur komunitas, Mangrove, Tanjung Kelapa